INTERAKSI SOSIAL PESERTA DIDIK BERKEBUTUHAN KHUSUS DENGAN PESERTA DIDIK REGULER (NORMAL) DI SMP NEGERI 23 PADANG - Mailiana, Aulia; Adiyalmon, Adiyalmon; Syafrini, Delmira (Pendidikan Sosiologi, 2014)
The majority of learners with special needs who are less able to communicate well with students of regular (normal). Learners with special needs (tuna bronze) communicate using sign language, learners with special needs (disabled) just sitting in the classroom when their friends again play outside of the classroom, while the students with special needs (tuna barrel) learners which is difficult to control the emotions and difficult to adapt to the existing environment, this study aims to describe the form of social interaction between learners with special needs learners regular (normal) in SMP 23 Padang.This type of research used in this research is descriptive research with quantitative analysis are located in Champaign Junior High School 23. The informants in this study amounted to 17 people includes 7 people with special needs learners, learners regular 7 (normal), 1 the inclusion teacher, and 2 teacher subjects through the study of engineering documentation, observation and interviews. Accuracy of data is tested using the data triagulasi, the data were analyzed with an interactive model that consists of data collection, data reduction, data display and conclusion.The results of this study are: interaction between learners with special needs learners regular (normal) is more directed to associative interactions, as seen when the learning activities in the classroom has been going well, as in the teaching and learning activities of learners regular (normal ) would help learners with special needs to be able to understand the lessons that are poorly understood as explained by the subject teachers. While the shape of the interaction of learners with special needs learners regular (normal) outside the classroom more leads kapada dissociative forms of interaction, as seen when participants with special needs learners prefer to remain aloof from friends that this normal due to learners with special needs do not trust myself to be able to build a good interaction with other regular friends.